2011
DOI: 10.1161/circep.111.962258
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic Localization and Autonomic Modulation of Atrioventricular Junctional Rhythm in Failing Human Hearts

Abstract: Background The structure-function relationship in the atrioventricular junction (AVJ) of various animal species has been investigated in detail, however less is known about the human AVJ. In this study, we performed high-resolution optical mapping of the human AVJ (n=6) to define its pacemaker properties and response to autonomic stimulation. Methods and Results Isolated, coronary-perfused AVJ preparations from failing human hearts (n=6, 53±6 years) were optically mapped using the near-infrared, voltage-sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 42 publications
(56 reference statements)
2
41
0
Order By: Relevance
“…However, to date, hemicyanine dyes are the most universally used and applicable VSDs available. Indeed, among the most recent new advances enabled by these dyes, there has been recording of deep aberrant activity patterns in human hearts from transplant patients (27,28) and recording V m spikes (∼1 ms) from individual dendritic spines (29)(30)(31).…”
mentioning
confidence: 99%
“…However, to date, hemicyanine dyes are the most universally used and applicable VSDs available. Indeed, among the most recent new advances enabled by these dyes, there has been recording of deep aberrant activity patterns in human hearts from transplant patients (27,28) and recording V m spikes (∼1 ms) from individual dendritic spines (29)(30)(31).…”
mentioning
confidence: 99%
“…Moreover, we found that both the fast and slow pathways are involved in anterograde and retrograde conduction. 10 …”
Section: Discussionmentioning
confidence: 99%
“…Optical mapping of the AVN area in six hearts explanted from patients with advanced heart failure demonstrated that in the absence of SA nodal activation, spontaneous pacemaking activity originates in the nodal-His region and/or the proximal His bundle [30]. After earliest activation in the proximal His and compact AVN, the wavefront moved in retrograde fashion through the fast pathway and slow pathway, with earliest atrial activation via the fast pathway.…”
Section: Optical Mapping Of the Human Avnmentioning
confidence: 99%
“…Importantly, it is clear that both the slow and fast pathways permit anterograde as well as retrograde conduction [30].…”
Section: Optical Mapping Of the Human Avnmentioning
confidence: 99%